Ubicamos lugares a través de puntos de referencia - Palacios Moran, Aura Milagros (2018)
This professional skills test is a job that leads Third Year Primary Level students to understand what it calls benchmarks in geographic or spatial location in certain locations. Significant learning of this topic and practice is important to help grade children define their own location or the establishment of a known or unknown address. Theoretical support underpins what is the Social Staff Area and its theme that contributes to the integral development of students. The area involves two fields: personal development and citizenship exercise. It also focuses on the competencies and capabilities to be developed, such as its standards by cycles and levels. Similarly, it conceptualizes so-called reference points, which is the theme of the class session. With regard to pedagogical sustenance, it defines what the thematic body is, the methodological phases of meaningful learning and the theoretical definition of what a learning session is, analyzing its elements and defining the assessment, its types and its Instruments.